Gestalt Counseling Theory, Modeling Techniques, Traveling Around through Scout Activities to Improve Personal Achievement and Personal Defence as a Profile of Pancasila Students - I Ketut Dharsana; Muhamad Safiul Umam (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The Pancasila student profile is the personality profile of Indonesian students who are lifelong students who are competent, have character and behave in accordance with the noble values of Pancasila. Students who have the Pancasila personality are reflected in their personal achievements and personal differences. The aim of this research is to test the effectiveness of Gestalt counseling theory using traveling modeling techniques through scout activities to improve personal achievement and personal defence as a Pancasila Student. This research design is true experimental, with a pretest-posttest control group design. The research population was 210 class X students at SMAN 1 Pagai Utara Selatan with an independent curriculum. The research sample was taken using random sampling techniques and random classes as an intact group so that four classes were obtained as research samples. Hypothesis testing uses a dependent sample/group t-test (paired) or commonly called a paired sample t-test. From the descriptive data analysis, it can be seen that there is a difference between the pre-test mean score and the post-test mean score. Based on the H1 t-test, the tcount was 10.546, while the ttable with db (N1 + N2) – 2 = 60 – 2 = 58 and a significance level of 5% (0.05) was 2.002. Meanwhile, for the H2 t-test, the tcount was 11.784, while the ttable with db (N1 + N2) – 2 = 60 – 2 = 58 and a significance level of 5% (0.05) was 2.002. So it can be concluded that based on the t-test H1 and H2 are accepted and H0 is rejected.